Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012 3rd IEEE International Conference on the Internet of Things 2012
DOI: 10.1109/iot.2012.6402302
|View full text |Cite
|
Sign up to set email alerts
|

Direct or indirect sensor enabled eco-driving feedback: Which preference do corporate car drivers have?

Abstract: The increasing demand for energy is rapidly exhausting our planet's natural resources (e.g. fossil fuels). Corporations with increasingly large car fleets significantly contribute to the volume of CO2 emissions released into the atmosphere. Further investigation is needed to help reduce this escalation in global warming utilizing eco-friendly yet cost effective measures. Internet of Things solutions, using sensor enabled feedback technologies with GPS and accelerometer, offer a medium which provides drivers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…For example, Darby [2] described the utility of accumulated household energy consumption feedback for assessing long-term patterns and trends for large energy loads and the impact over time of equipment investments or other changes; whereas instantaneous data can reveal impacts of behavior with respect to smaller end-uses. In the context of eco-driving feedback, studies have shown instantaneous feedback (e.g., momentary fuel efficiency) is used primarily for experimentation and learning new behaviors, whereas accumulated feedback (e.g., average fuel-efficiency) is used primarily for goal-setting and assessing overall performance [39,40]. As mentioned later with regard to feedback standards, it is also useful to provide information at multiple time scales for comparison [25].…”
Section: Data Granularitymentioning
confidence: 99%
“…For example, Darby [2] described the utility of accumulated household energy consumption feedback for assessing long-term patterns and trends for large energy loads and the impact over time of equipment investments or other changes; whereas instantaneous data can reveal impacts of behavior with respect to smaller end-uses. In the context of eco-driving feedback, studies have shown instantaneous feedback (e.g., momentary fuel efficiency) is used primarily for experimentation and learning new behaviors, whereas accumulated feedback (e.g., average fuel-efficiency) is used primarily for goal-setting and assessing overall performance [39,40]. As mentioned later with regard to feedback standards, it is also useful to provide information at multiple time scales for comparison [25].…”
Section: Data Granularitymentioning
confidence: 99%
“…However, research has rarely considered mobile-only solutions for EDFIS. We have found only two corresponding contributions [5,19]. Indeed, mobile EDFIS can make an essential contribution to the avoidance of CO 2 emissions, especially in emerging trends such as car sharing [20].…”
Section: Introductionmentioning
confidence: 77%
“…Based on additional available information, drivers can adapt to their behavior. As different studies show, it is possible to reduce fuel consumption through feedback systems by between 1 and 7% on average (e.g., [5,6]).…”
Section: Introductionmentioning
confidence: 99%
“…Y. K. Joo and J.-E. R. Lee investigated the use of an in-vehicle voice agent to promote eco-driving [37]. Another study used an eco-driving smartphone application called DriveGain in a driving simulator, concluding that using such a support tool reduced fuel consumption by 16% [38].…”
Section: Introductionmentioning
confidence: 99%